Problematika Penulisan Huruf Tegak Bersambung dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar Bagi Kelas Rendah (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
Indonesian is a subject that emphasizes reading and writing skills, including cursive writing for elementary school students. However, many students experience difficulties in cursive writing, especially in grade 3 of SD Negeri 1 Bae. This study aims to analyze students' difficulties in cursive writing and teachers' efforts to overcome them through peer teaching strategies. This study used a qualitative descriptive approach with teachers and grade 3 students of SD Negeri 1 Bae as research subjects. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results showed that difficulties in cursive writing in students were caused by weak fine motor skills, inconsistent letter shapes, inaccurate letter sizes, and low motivation and self-confidence. The application of peer tutoring strategies was proven to be effective in improving writing skills, making students' writing neater, improving letter proportions, and increasing students' enthusiasm and self-confidence. In addition, peer tutored students also showed increased responsibility and empathy towards their peers. Based on these findings, peer tutoring strategies can be an effective alternative to improve cursive writing skills in elementary school students.